2008
DOI: 10.1088/0957-4484/19/04/045703
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the energy dissipation in dynamic force microscopy

Abstract: Abstract. The dissipation of energy in dynamic force microscopy is usually described in terms of an adhesion hysteresis mechanism. This mechanism should become less efficient with increasing temperature. To verify this prediction we have measured topography and dissipation data with dynamic force microscopy in the temperature range from 100 K up to 300 K. We used 3,4,9,10-perylenetetracarboxylic-dianhydride (PTCDA) grown on KBr(001), both materials exhibiting a strong dissipation signal at large frequency shif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
7
3
Order By: Relevance
“…However, because the number o possible physical phenomena in any simple system is limited, we can expect to observe the same physical mechanism inducing noncontact friction in analogous systems involving other materials. In fact, at least for small tip-sample separations, energy dissipation of the same order of magnitude has been observed for other tipsample materials combination involving metals, semiconductors and insulators [1,8,9]. It is this possibility that makes the present investigation more relevant, since the results and conclusions can be valid for other systems of practical interest.…”
Section: Introductionsupporting
confidence: 56%
“…However, because the number o possible physical phenomena in any simple system is limited, we can expect to observe the same physical mechanism inducing noncontact friction in analogous systems involving other materials. In fact, at least for small tip-sample separations, energy dissipation of the same order of magnitude has been observed for other tipsample materials combination involving metals, semiconductors and insulators [1,8,9]. It is this possibility that makes the present investigation more relevant, since the results and conclusions can be valid for other systems of practical interest.…”
Section: Introductionsupporting
confidence: 56%
“…However, by changing measurement parameters (i.e., bias voltage, oscillation amplitude, temperature, and species of surface atom), a selected contribution can be emphasized. [12][13][14][15] In order to reduce the viscous damping and to study the atomic adhesion, setting the velocity of the cantilever slower is effective; namely, usage of a low-frequency cantilever with a smaller amplitude, because the velocity of the cantilever is described as v(t) = 2πf A sin(2πf t), where f is the oscillation frequency, A is the oscillation amplitude, and t is the time. In 2001, Hoffmann et al studied the atomicscale energy dissipation with their off-resonance technique (f = 1 kHz and A < 20 pm), in which the low-frequency and small-amplitude method successfully reduced the effect of the viscous damping, and claimed that the dynamic dissipation in the noncontact region is likely due to the motion of a bistable atomic defect in the tip-sample region.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Among candidate molecules, 3,4,9,10-perylenetetracarboxylic-dianhydride ͑PTCDA͒ is a prototype organic semiconductor that has been increasingly studied on insulating surfaces to provide the electrical isolation of the molecule from the substrate essential for device performance. [5][6][7][8][9][10][11] In general, characterization of molecular ordering on the surface requires high-resolution imaging and is only possible on insulating surfaces with noncontact atomic force microscopy ͑NC-AFM͒. 12 Earlier studies have shown that PTCDA islands with a well-defined herringbone arrangement form preferentially at the bottom of step edges.…”
Section: Introductionmentioning
confidence: 99%